Fresno Merced Counties Legal Services Baby Shower For Leroy and Joanna Cordova - Watkins, Howard::::::::: (1982)
Alicia Cordova and Christine Burnes in office hallway; staff mailboxes; metal file cabinets American Law Reports 2nd and 3rd on shelves